The Effect Of Used Cricket Flour (Gryllus Sp) In Feeding Of Kokok Balenggek Cocks On The Number, Duration, And Frequency Of Crowing Crowning For 12 - 24 Weeks - Dara Surtina; syahro ali akbar; Faisal Faisal (Journal of Animal Nutrition and Production Science, 2022)
This study aims to determine the effect of using cricket flour (Gryllus sp) in the diet on the number, duration, and frequency of crowing crowning of balenggek cocks for 12-24 weeks. This study used 48 male balenggek crowing cocks which were given additional cricket flour diets. The completely randomized design (CRD), with 4 treatments, was used as the experimental design in this research. The treatments were: PO (no cricket flour), Pl (used cricket flour 2%), P2 (used cricket flour 4%), and P3 (used cricket flour 6%). Each treatment was repeated 4 times and each replication consisted of 3 male kokok balenggek cocks. The variables measured in this study were the number of crowings, duration, and frequency of crowing of kokok balenggek cocks at 12-24 weeks of age. The results showed that the addition of cricket flour in the ration had a significantly different effect (P<0.05) on the number of crows and the duration of crowing, and a very significant effect (P<0.01) on the crowing frequency of balenggek cocks at the age of 12- 24 weeks with the best number of crowings, duration, and frequency of crowing was in P3 (was used of 6% cricket flour)